A cross‐flow rotating packed bed toward desulphurization of marine exhaust gas. (16th December 2021) - Cai, Yong; Li, Yan‐Bin; Fei, Jia; Luo, Yong; Wen, Zhang‐Nan; Chu, Guang‐Wen
Abstract: The marine exhaust gas containing SO2 leads to serious impacts on human health and marine environments. Due to the strict emission standard of marine exhaust gas and the limited space of ships, desulphurization process intensification is urgent. Herein, a cross‐flow rotating packed bed (CF‐RPB) with a compact size was developed toward desulphurization of marine exhaust gas. According to the emission standards of different sea areas, the characteristics of simulated open seawater desulphurization (OSD) and closed alkali desulphurization (CAD) were systematically evaluated. The respective correlations for K y a of OSD and CAD were proposed to predict the height of CF‐RPB. The desulphurization efficiencies of 86% in the OSD and 97% in the CAD were achieved in a three‐stage CF‐RPB, satisfying the emission standard. Compared with the traditional spray tower, the CF‐RPB has a higher mass transfer coefficient with a smaller volume, which has great potential for desulphurization of marine exhaust gas. Abstract : Structure and desulphurization performance of the cross‐flow rotating packed bed in a marine environment.